The image of Kazakhstan in Chinese periodicals (based on the analysis of news content in the newspaper «Zhjen'min' Zhibao» from 2018 to 2022) (Herald of Journalism, 2023)
The proliferation of science and technology has resulted in an amplified impact of the media on the formation of state's image. To some extent, state's image is reflected in the news coverage provided by the international media. As Kazakhstan's comprehensive national strength continues to grow, and its international status continues to improve, the country has garnered increased attention from the foreign media.The aim of the research is to examine the international image of Kazakhstan by analyzing its portrayal in the abovementioned Chinese newspaper. Through a systematic review and analysis of the content, sources, and volumes of “Zhjen'min' zhibao” coverage over the past five years, this study seeks to categorize Kazakhstan's image in terms of its political, economic, cultural and social aspects, with an emphasis on the state's relationship with China.Research methodology: collection of articles, data and information from “Zhjen'min' zhibao”, systematic analysis, synthesis.According to the research, the Kazakhstan's image in the Chinese media is that of a «rapidly developing peaceful power» with a positive political image, an image of comprehensive strategic partnership, a positive economic image, and a cultural image that emphasizes cultural exchange.The research holds significant scientific and practical value as it sheds light on the state image of Kazakhstan, which can serve as a basis for predicting how other nations will perceive the country in the future. It will help Kazakhstan and China strengthen mutual understanding, political, economic, cultural and other areas of cooperation, and it will also be of great practical significance in promoting cultural exchanges and deepening friendship between the two countries.The value of the research work is to help Chinese audiences understand Kazakhstan, improve Kazakhstan's image in China and promote cooperative development. Overall, the study is valuable in promoting intercultural communication in Kazakhstan.Keywords: publications, “Zhjen'min' zhibao”, Kazakhstan, state image